A comprehensive study on the performance and emission characteristics of a diesel engine with the blends of diesel, jojoba oil biodiesel, and butylated hydroxyl anisole as an alternative fuel. Issue 2 (1st June 2023) - Viswanathan, Karthickeyan; Paulraj, Arulraj
ABSTRACT: Supplementary requests for nonrenewable-based fossil fuel and a massive increase in atmospheric air quality, due to the excess dependency on nonrenewable fuel especially diesel, offered a view to find energy production from a renewable resource for the unaltered compression-ignition engine. The present work intends to evaluate the engine characteristics, namely, emission and performance of a Jojoba oil biodiesel (JB100) fueled diesel engine with Butylated hydroxyl anisole (BHA) as an antioxidant at distinct mass fractions (50, 75, and 1000 ppm). The experimentation was conducted in a single cylinder, water-cooled, direct injection compression ignition (DICI) diesel engine with 1500 rpm at constant speed. The experimental work on the compression-ignition engine revealed that the blending of BHA to JB100 leads to improved engine efficiency through diminished fuel utilization. The findings exhibited that the addition of BHA leads to an upgraded production of emission levels from the engine (especially hydrocarbon, carbon monoxide, and smoke). BHA addition to JB100 has a substantial effect on decreasing NOx emission. JB100+ BHA1000 showed lower NOx compared to all other prepared fuel samples. Based on experimentation, JB100 was observed as a noticeable substitute for conventional fuel and BHA presence helps to improve the performance and emission parameters. JB100+ BHA1000 sample was deliberated advantageous compared to JB100+ BHA750 and JB100+ BHA500 based on its engine characteristics.